MANAJEMEN KURIKULUM ANAK USIA DINI DALAM MENUMBUHKAN KARAKTER MANDIRI SISWA - Muh. Hasyim Rosyidi; Hidayatul Mufidah; Nisa'ul Mufaridoh (Universitas Islam Lamongan, 2022)
Early childhood education is very important because the potential for intelligence and basic behavior of children is vulnerable at this age, the importance of this age is often referred to as the golden age. The researcher concludes that the child's development at the next stage is the child's productivity to develop according to stimulation, guidance, assistance and treatment in accordance with the level of developmental growth.Researchers know the problems and get accurate data, researchers use the method of observation (field observations), interviews or interviews and documentation. By using qualitative descriptive analysis techniques. The results of the research in curriculum management are that management functions are applied, including the curriculum management planning process that follows the Indonesian Early Childhood Education Association (HIMPAUDI). Curriculum planning is carried out with the preparation of teaching and learning process materials. The implementation of the curriculum is carried out without any necessity, but rather on direction so that students can have an independent character. The supervision and evaluation of this curriculum consists of several stages, namely: measuring the implementation of the curriculum, measuring the implementation of real activities and analyzing errors or deficiencies that exist during carrying out the curriculum, through meetings once a semester with HIMPAUDI.Inhibiting factors in curriculum managementearly childhood in improving the independent character of students, namely, students still want to be close to their parents when they are at school. Supporting factors in curriculum management improve independent character, namely students playing while learning with learning media at school and from the factor of their parents who also provide enthusiasm in the learning process.